Clima organizacional y satisfacción laboral en las empresas medianas y grandes del Sector Lácteo cantón Latacunga. - Llamba Llamba, Aracely Estefanía (2018)
The work environment and the job satisfaction in the medium and large companies of the dairy sector in Latacunga, was established if there is a correlation between the variables to be treated. The objective of the research was to determine If the work environment affects the job satisfaction of the workers of the dairy companies, for which the dimensions such as internal communication, recognition, interpersonal relationships at work, decision making, physical environment, commitment, adaptation to change, delegation of activities and functions, external coordination and efficiency in productivity that are fundamental pillars for medium and large companies in the dairy sector in Latacunga. The investigative method applied was from the quantitative, descriptive-correlational research approach that was used with the survey technique and whose instruments were the work environment measurement of the authors Chiang, Núñez and Salazar and the job satisfaction instrument of the authors Meliá & Peiró; the data collected were tabulated in the statistical software SPSS. The population studied was 148 employees of the companies under study. The degree of reliability for the scale of the two applied instruments from variables: Work environment in Cronbach's alpha was 0.977 and in job satisfaction in Cronbach's alpha it was 0.935. The result obtained from this study is a Pearson correlation coefficient r of 0.957 that is considered as an effective relationship, this means that the variables organizational climate and job satisfaction are related in a positive way. The research generated in the medium and large companies of the dairy sector in Latacunga a social impact which helps to meet the goals set by the company and that workers can achieve their personal goals.